Does openness really incentivize openness? - Greve, T. (Harvard University, 2020)
In reason years, articles from a number of highly regarded magazines and journals have been discussing the benefits of openness in drug discovery as a way to reduce duplication of effect and development cost. Openness is being presented as open source, open data, open access and/or open science, where the later demands that internal laboratory notes are freely available and methods are shared, and hence, this concept opens up for a practice where others can contribute to an ongoing research. Basically, these so-called openness paradigms aim to enhance collaboration between different agents (e.g., companies and universities) with common interest in working together to develop new products/services, such as drugs. In this article, we go a step back to analyse whether or not openness really enhance collaboration between agents and if not, what can be done to restore the goal of these paradigms. We use game theory to analyse the mindset and behavior of the pharmaceutical industry.